Molecular basis for the mechanism of action of an anti-TACE antibody. Issue 8 (16th November 2016) - Peng, Li; Cook, Kimberly; Xu, Linda; Cheng, Li; Damschroder, Melissa; Gao, Changshou; Wu, Herren; Dall'Acqua, William F.
ABSTRACT: Inhibitors of tumor necrosis factor-α converting enzyme (TACE) have potential as therapeutics for various diseases. Many small molecule inhibitors, however, exhibit poor specificity profiles because they target the highly conserved catalytic cleft of TACE. We report for the first time the molecular interaction of a highly specific anti-TACE antagonistic antibody (MEDI3622). We characterized the binding of MEDI3622 using mutagenesis, as well as structural modeling and docking approaches. We show that MEDI3622 recognizes a unique surface loop of sIVa-sIVb β-hairpin on TACE M-domain, but does not interact with the conserved catalytic cleft or its nearby regions. The exquisite specificity of MEDI3622 is mediated by this distinct structural feature on the TACE M-domain. These findings may aid the design of antibody therapies against TACE.